Vloga trombocitov pri nastanku zasevkov raka - Smrdel, Lara (Farmacevtski vestnik, 2025)
Cancer represents a heterogeneous group of diseases characterized by uncontrolled cell proliferation and invasion. Over the past decade, research has shown that, in addition to regulating hemostasis, platelets interact with tumour cells, contributing to their survival in circulation and facilitating colonization in secondary organs. The interaction between platelets and tumour cells occurs through direct cell contacts and the release of bioactive mediators. Given the important role of platelets in cancer metastasis, therapeutic strategies targeting platelet–tumour cell interactions are being explored. Potential approaches include inhibitors of platelet activation, monoclonal antibodies against adhesion molecules, and angiogenesis inhibitors. While these strategies hold promise for improving the outcomes in cancer treatment, further research is needed for clinical implementation.
Keywords: cancer progression; Farmakoterapija; metastasis; Metastaze; napredovanje raka; platelets; Rak (medicina); terapevtski pristopi; therapeutic approaches; trombociti; zasevanje